2022
DOI: 10.1108/qrj-11-2021-0127
|View full text |Cite
|
Sign up to set email alerts
|

Extended qualitative content analysis: researching the United Nations and other international institutions

Abstract: PurposeThis paper aims to introduce the extended qualitative content analysis (EQCA) method to integrate data-reducing and data-complicating research steps when conducting qualitative research on the United Nations and other international institutions.Design/methodology/approachEQCA supplements the method of qualitative content analysis, which enables researchers to deal with large amounts of data, with two elements from grounded theory, which allow detailed analysis and interpretation of codes and sub-codes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…We therefore use the integrative approach of an extended qualitative content analysis (Mende 2022) that combines elements of both qualitative content analysis (Schreier 2012) and grounded theory (Strauss and Corbin 1998). This approach captures both the explicit and implicit elements of hidden discursive contestation.…”
Section: Methodological Demandsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore use the integrative approach of an extended qualitative content analysis (Mende 2022) that combines elements of both qualitative content analysis (Schreier 2012) and grounded theory (Strauss and Corbin 1998). This approach captures both the explicit and implicit elements of hidden discursive contestation.…”
Section: Methodological Demandsmentioning
confidence: 99%
“…12 Both cases entail an extensive corpus of data that we assessed separately, while ensuring intracoder and intercoder consistency by closely cooperating on the collection, comparison, compilation and interpretation of data from both cases (Thomas and Harden 2008). We applied the method of extended qualitative content analysis to combine a deductive, classificatory method with an interpretive, inductive approach (Mende 2022). This entailed several rounds of coding.…”
Section: Case Studies In the United Nations And International Labour ...mentioning
confidence: 99%
“…While quantitative methods focus on counting and measuring variables such as words, news articles, and messages, qualitative techniques can add richness and depth to the analysis by identifying patterns and themes [ 70 ]. When conducted systematically, qualitative content analysis can produce insightful interpretations of the text or subject matter, highlighting prominent categories and emerging themes [ [70] , [71] , [72] ]. As prior research has shown, using a qualitative approach can be beneficial for studying different aspects and case studies on social media [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…Con el análisis de contenido, se lleva a cabo un estudio detallado de la interpretación de códigos y subcódigos, destacando especialmente la codificación axial y el muestreo teórico. En conjunto, estas características hacen del análisis de contenido una herramienta valiosa y potente para cualquier investigación que busque explorar la complejidad y riqueza de los datos cualitativos (Kyngäs, 2020;Lindgren et al, 2020;Mende, 2022).…”
Section: Materiales Y Métodosunclassified